BUDAYA KONSUMTIF PELAJAR SMA DI PAKU URE III KECAMATAN TENGA KABUPATEN MINAHASA SELATAN - Potu, Derby David (Universitas Sam Ratulangi, 2016)
The situation and current condition that has been increasingly modern and also the more interesting by offering shopping center, should not be denied that the community including in it are high school students trying to do business to be able to adapt and try to follow with maximum this progress and strive are all the desirable despite often had to forced passing ability or ability. Lifestyle patterns often found on the Manado society, namely lifestyle hedonic is a lifestyle activity to find life, as spend more time outdoors, more play, delight at the crowd, happy to buy expensive things ones, and always wanted to be the limelight. Growth of the capital city Amurang and Manado who has presented shopping center that have become more complete and also all make high school students are now in greater often expenditure even happy shopping. Conditions is quite support the behavior consumptive high school students. Culture consumptive students in the Pakuure III village, because the economic condition family / parents enough. The culture consumptive happened social changes to Pakuure III villagers, namely lifestyle students followed peoples lifestyle urban. Keywords : lifestyle, student, consumptive